Pharmaceutical organic salt: Disordered crystal structure of levofloxacin with γ-resorcylic acid - Mashhadi, Syed Muddassir Ali; Tahir, Muhammad Nawaz; Apperley, David; Bhatti, Moazzam Hussain; Ashfaq, Muhammad; Yunus, Uzma (European Journal of Chemistry, 2021)
This study reports an organic salt prepared from an antibacterial drug, levofloxacin and antioxidant γ-resorcylic acid. A simple preparation method leads to a crystal with disordered structure. The idea is to prepare an organic salt comprising of pharmaceutically acceptable acidic and basic components. The salt is characterised by IR, solid state NMR, and single crystal XRD. Crystal data for C25H26N3O8F: triclinic, space group P-1 (no. 2), a = 7.0037(8) Å, b = 12.764(3) Å, c = 13.909(3) Å, α = 104.821(4)°, β = 92.039(4)°, γ = 95.334(4)°, V = 1194.6(4) Å3, Z = 2, T = 296(2) K, μ(MoKα) = 0.113 mm-1, Dcalc = 1.433 g/cm3, 16879 reflections measured (5.048° ≤ 2Θ ≤ 54.186°), 5139 unique (Rint = 0.0663, Rsigma = 0.0975) which were used in all calculations. The final R1 was 0.1121 (I>2σ(I)) and wR2 was 0.2505 (all data). SC-XRD analysis shows that the crystal packing is stabilized by strong H-bonding of type N-H···O and comparatively weak interactions of type C-H···O, C-H···π and off-set π···π stacking.